High‐Frequency Geomagnetic Fluctuations at Auroral Oval and Polar Cap. Issue 8 (18th August 2018) - Peitso, P.; Tanskanen, E. I.; Pulkkinen, T. I.; Mursula, K.
Abstract: Rapid magnetic fluctuations are known to be closely linked to the high‐latitude geomagnetic activity, in particular, to geomagnetic pulsations and subtorms. Increasing amount of commercial activity in the arctic regions requires better monitoring capability and improved understanding on the effects of geomagnetic hazards to infrastructure. In this study, we analyze rapid, 1‐s fluctuations in Greenland. To measure high‐frequency geomagnetic fluctuations in the auroral oval and polar cap, we use high time resolution data of 1 s from 12 stations covering a large latitudinal range of 64 to 84 quasi‐dipole geomagnetic latitude (QDGMlat). We found out that the large magnetic field fluctuations exceeding 0.2 nT/s are observed 10–30% of the time in auroral oval latitudes, depending on the solar cycle phase and station location. The latitudinal differences are much larger in fluctuation coverage (fractional derivative rate, FDR) than in fluctuations amplitude (d H /d t ). The highest |d H /d t | and FDRs at noon are observed at the northern stations from 72 to 84 QDGMlat, while in south Greenland from 72 to 65 QDGMlat, the highest |d H /d t | and FDRs are recorded at midnight. The largest differences in seasonal variation between noon and midnight are observed in the polar cap, where a summer increase is seen at noon and almost flat seasonal profile at midnight. Plain Language Summary: We analyze Earth's magnetic field measurements from Greenland in 2011–2013. We use high time resolution measurements obtained from 12 stations, covering a large geographic area. We use the rate of change of the magnetic field as the basis of our analysis, and we have developed a new method called the fractional derivative rate for this purpose. Differences between the years, time of day, and geographic location along the north‐south axis are studied separately. We found out that there are significant differences between the stations, with the northernmost stations being more magnetically active during noon and the southernmost stations more active during midnight. The largest differences in these activity patterns are seen in the northernmost area, the polar cap. Understanding these variations in activity between the geographic locations will help us prepare more accurate and better targeted space weather forecasts in the future. Key Points: The largest differences in seasonal variation between noon and midnight are seen in the polar cap Midnight hosts most fluctuations below 72 and noon above 72 degrees geomagnetic latitude Latitudinal differences are larger in fluctuation coverage (FDR) than in amplitude (d H /d t )